Hyperprolactinemia in patients with chronic kidney disease - І.О. Dudar; V.M. Savchuk; О.М. Loboda; E.K. Krasiuk (Ukrainian Journal of Nephrology and Dialysis, 2021)
Despite rapid progress in improving dialysis technology in recent years, mortality in hemodialysis (HD) patients remains quite high. The main reasons are cardiovascular disease. The search of factors that are associated with an increased risk of adverse clinical events in patients with chronic kidney disease (CKD) is an urgent problem of modern nephrology.Prolactin (PL) is a unique hormone that can perform the functions of both a hormone and a neuropeptide. Among patients with CKD, the frequency of hyperprolactinemia (HPL) increases with decreasing glomerular filtration rate (GFR). There is a moderate HPL due to impaired degradation of PL in the kidneys. Hemodialysis does not affect the level of PL. A negative correlation between the levels of PL and GFR, PL and albumin levels and PL and Hb levels are shown in the studies. Serum PL is positively correlated with blood pressure and the risk of cardiovascular events.Despite the relatively high prevalence of HPL in patients with CKD, particularly in the dialysis population, there is uncertainty about the consequences of this condition for this cohort of patients. Further studies are needed to study the effects of HPL on clinical outcomes in patients with CKD. If a causal relationship between HPL and clinical outcomes, in particular cardiovascular events, is shown, HPL may be a potential target for therapeutic interventions.